Defining "occludable" angles in population surveys: drainage angle width, peripheral anterior synechiae, and glaucomatous optic neuropathy in east Asian people. Issue 4 (18th March 2004) - Foster, P J; Aung, T; Nolan, W P; Machin, D; Baasanhu, J; Khaw, P T; Alsbirk, P-H; Lee, P S; Seah, S K L; Johnson, G J
Abstract : Background/aim: A current consensus in epidemiological studies of primary angle closure (PAC) is to diagnose the condition only if the posterior (usually pigmented) trabecular meshwork is seen for less than 90° of the angle circumference, termed an "occludable angle." The authors sought to assess the validity of this epidemiological classification by exploring the relation between drainage angle width, peripheral anterior synechiae (PAS) and glaucomatous optic neuropathy (GON). Methods: 918 Mongolians and 995 Chinese Singaporeans, both groups aged 40 years and older were examined in two population based surveys. Gonioscopic angle width was graded in five categories (0 = closed to 4 = wide open) according the scheme described by Shaffer. Cases with secondary PAS were excluded. Results: The rate of PAS was between 0.3% and 1.7% in people with wide angles (grades 3 and 4). In those with grade 2 angles, PAS were seen in between 8% of eyes. In eyes with grade 1 angles, the rate rose to 17% in Chinese Singaporeans, and 31% in Mongolians. The odds of PAS were higher in people with narrower angles. However, there was a greater absolute number of people with PAS whose drainage angles were classified as "not occludable" than those classified "occludable." Conclusions: The traditional view that primary angle closure becomes a significant possibility in drainage angles of ⩽ grade 2 (approximately 20°) is valid in east Asians. The definition of an "occludable" angle examined here excludes many people with PAS. This probably serves to underemphasise the role of PAC in population surveys of glaucoma prevalence in Asian people.